COMMISSION FOR BALANCE AND NIC 18 ¿THIS BENEFITS TO MEMBERS OR TO THE AFP? - Romero Cerna, José Salvador (2014)
The recent reform of the private pension system in-corporates, among other changes the commission on the balance of the administered funds (commission for balance) in replacement of the Commission on the remuneration (commission flow) charged by the Pension Fund Administrators (AFP ) affiliates, and the gradual implementing of NIC 18 Revenue.The article aims to determine whether changes incor-porated benefit to affiliates or the AFP. To do this, the differences between the proposed government reform and reform finally approved, as well as its impact on the members and the AFP are reviewed.